THE MEANING OF SIGNS ON TATTOO ON CAST IN “CITY OF BONES” MOVIE - Nasir, Nurzakinah; Halim, Abdul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This research discusses tattoos in the City of Bones movie. A tattoo is the art of tattooing the body with various themes or more themes that are poured on the upper part of the body skin to become works of art, which for the owner of the tattoo is a sign of pride or a meaningful warning. There are 10 signs in the movie, namely: calm angers mean emotion control, angelic power means removing traces, deflect means helper from attack, speed means to supporting or giving strength to other tattoos, stamina means power, soundless means moving without being noticed, fortitude means inner strength, vision means making the enemy have no power, strength means energy, and iratze heal means healing. This research is expected to help the reader understand the meaning of the signs mentioned in the film. The researcher used a qualitative research and descriptive method in conducting this research. The researcher used this method because the research objective describes the data in the spoken or written text. The results of this study indicate that the tattoos in the movie have meaning, but the tattoos are only used for movies because the City of Bones movie was fiction and unrelated to the real world.